Experience with return voltage measurements for assessing insulation conditions in service-aged transformers. - Saha, T.K.
This paper describes the investigation of the insulation condition of a number of power and distribution type transformers of different manufacturing dates and with different operating histories. Return voltage measurements were conducted for these transformers. Effects of moisture and aging on the oil-paper insulation of these transformers were investigated and results are presented in this paper. Moisture in oil samples at known temperature was measured for these transformers. Previously accelerated aging experiments were performed on paper wrapped insulated conductors in different environments over a temperature range of 115 to 145°C. Results from the measurements on transformers are compared with those of the accelerated aged samples and are described in this paper.
Keywords: 115 to 145 C; Aging; Condition monitoring; Dielectric measurement; Insulation life; Moisture; Oil-paper insulation; Paper wrapped insulated conductors; Return voltage measurements; Service-aged transformer insulation condition assessment